Internal audit function, board quality and financial reporting quality: Evidence from Malaysia - Johl, S.K. (2013)
The purpose of this paper is to test the impact of the internal audit function (IAF), an increasingly common internal governance mechanism, on a firm's financial reporting quality. Specifically, this paper investigates the association between the quality of the IAF and abnormal accruals (as a proxy for financial reporting quality) and whether the board of directors play a role in moderating the relationship. This paper uses a unique dataset of survey responses and archival data. Regression analysis was used to test their hypotheses. Although their initial findings show an unexpected positive relationship between internal audit quality and abnormal accruals, this relationship is contingent on whether firms outsource their internal audit activities and/or whether they are politically linked. In estimations excluding outsourcing and political connections observations, this paper shows that the association between internal audit quality and abnormal accruals is negative and in particular internal audit organisational independence, financial focus audit activities and investment are associated with lower income-increasing (opportunistic) abnormal accruals. Next, when this paper interact board quality with internal audit quality, this paper finds although the lower ordered variables board quality and internal audit quality coefficients are negatively related to abnormal accruals, the interaction variable between these two variables is positively associated with abnormal accruals, indicating the possibility of a substitution relationship between board quality and internal audit quality. Their findings show that certain internal audit attributes play an important role in the financial reporting process and thus these findings are expected to inform the Institute of Internal Auditors and other regulatory bodies on the role of internal audit (being an important internal governance mechanism) in financial reporting, which in turn can assist in market/regulatory reforms/changes and inform the revised Malaysian Code of Corporate Governance. This paper extends prior internal auditing literature by examining the relationship between internal audit quality and financial reporting quality in the context of a developing country, namely Malaysia, and whether the board of directors moderate the examined association. Â© 2013, Emerald Group Publishing Limited